Polydopamine Sensors of Bacterial Hypoxia via Fluorescence Coupling. (3rd November 2020) - Lee, Joo Hoon; Ryu, Jea Sung; Kang, Yoo Kyung; Lee, Haeshin; Chung, Hyun Jung
Abstract: Biological catecholamines play critical physiological roles in various parts of the human body, namely, the skin and brain. In the skin, an oxygen‐contacting and oxygen‐abundant body part, catecholamine molecules are oxidatively polymerized, becoming melanin. In contrast, the brain is an oxygen‐demanding organ that suppresses catecholamine oxidation. Catecholamine oxidative polymerization, also known as polydopamine (or dopamine–melanin) formation, can be finely controlled by bacterial growth. Under exponential growth of Escherichia coli, a process that requires large amounts of oxygen, dopamine polymerization is significantly inhibited. In contrast, under steady‐state growth, polydopamine is formed due to the abundance of oxygen which is not actively consumed by E. coli . This polydopamine‐oxygen relationship is further demonstrated by using fluorescent dextran nanoparticles (FDNPs) as sensors, whose fluorescence is quenched by polydopamine formation. Thus, FDNP fluorescence can be precisely controlled by dopamine concentration, incubation time, and bacterial number. The cascade coupling of E. coli growth—oxygen level—polydopamine—fluorescence can also be used to detect the antibiotic‐resistant bacteria, New Delhi metallo‐beta‐lactamase 1‐positive (NDM1+) E. coli . This method not only uncovers the unique role played by biological catecholamine in a living system, but also presents a diagnostic assay for detecting bacterial growth and antibiotic susceptibility. Abstract : Biological catecholamines play critical roles in the human body, and vary in oxidative polymerization rates depending on their function in different tissues. This study reports a fluorescence coupling strategy to demonstrate the polydopamine–oxygen relationship during bacterial growth‐induced hypoxia. The rate and extent of polydopamine formation can be finely controlled according to the bacterial growth condition, as well as antibacterial effects.